Incidence of postcesarean infections in relation to HIV status in a setting with limited resources - Björklund, Kenneth; Mutyaba, Twaha; Nabunya, Evelyn; Mirembe, Florence (Acta Obstetricia et Gynecologica Scandinavica, 2005)
The aim of the present study was to assess the incidence of postcesarean infections in relation to HIV status in a setting where resources are limited, HIV infection is common, and antiretroviral treatment is not generally available. Methods. The setting was a tertiary African obstetric unit with 27 000 deliveries annually. The study design was prospective and the sample consisted of 1600 of cesarean sections. All women requiring cesarean section were eligible for inclusion. HIV status was registered from the antenatal card only. For the analysis, the participants were divided into two categories: those with negative or unknown HIV status and those with positive HIV status. The main outcome measures are endometritis, wound infection, and mobilization parameters. Results. A total of 1526 cases, of which 1492 were emergency cesarean sections, were included in the analysis. HIV status was negative or unknown in 1430 cases and positive in 96. In the HIV-negative/unknown group, the incidence of endometritis was 8.5% (121/ 1430), wound infection 5.0% (71/1430), and endometritis and/or wound infection 10.8% (154/1430). In the HIV-positive group, the corresponding incidences were 51.0% (49/96), 29.2% (28/96), and 65.5% (63/96), respectively. The indication for cesarean section was dystocia in 79% (134/170) of the women who developed endometritis. Conclusions. The results indicate that women with untreated HIV infection are at very high risk of postcesarean infection in low resourced settings.
Keywords: Cesarean section; Endometritis; Wound infection; HIV